Role of ACE2 genetic polymorphisms in susceptibility to SARS-CoV-2 among highly exposed but non infected healthcare workers. Issue 1 (1st January 2021) - Martínez-Sanz, Javier; Jiménez, Daniel; Martínez-Campelo, Laura; Cruz, Raquel; Vizcarra, Pilar; Sánchez-Conde, Matilde; Ron, Raquel; Rodríguez, Mario; Herrera, Sabina; Moreno, Santiago; López-Huertas, María Rosa; Serrano-Villar, Sergio
Abstract: We aim to evaluate the role of single-nucleotide polymorphisms of the angiotensin-converting enzyme 2 in susceptibility to SARS-CoV-2 infection. We included 28 uninfected but highly exposed healthcare workers and 39 hospitalized patients with COVID-19. Thirty-five SNPs were rationally selected. Two variants were associated with increased risk of being susceptible to SARS-CoV-2: the minor A allele in the rs2106806 variant (OR 3.75 [95% CI 1.23–11.43]) and the minor T allele in the rs6629110 variant (OR 3.39 [95% CI 1.09–10.56]). Evaluating the role of genetic variants in susceptibility to SARS-CoV-2 infection could help identify more vulnerable individuals and suggest potential drug targets for COVID-19 patients.